Newspapers as Instruments for Building Literate Communities: The Nigerian Experience (Nordic Journal of African Studies, 2002)
This paper recognizes newspapers, the world over, as useful tools for promoting literate communities. Because of their invaluable functions of informing, educating, entertaining and constructively bringing the activities of the government nearer to the people, newspapers are now very popular and common with adults and young alike. Newspapers are veritable tools for promoting literacy through reading, writing and dialogues (among readers and critics), which are the hallmarks of effective and efficient use of language. Newspapers have a built-in capacity to motivate readers. As a result, it is the common practice in most parts of the country to have people congregate around newspapers stands and vendors every morning reading and discussing the contents of the newspapers. Newspapers can thus promote critical thinking, retention of information, problem solving and questioning of information source.This paper is an account of an on-going study regarding the effectiveness and non-effectiveness of English medium newspapers for facilitating literacy empowerment.Given the need to exploit the enormous resources of newspapers, as vehicles for facilitating literacy empowerment among literate communities, this paper suggests steps that can be taken by newspaper publishers, members of the Nigerian education orchestra and the Nigerian polity in appropriating the catalytic role of the newspaper as an instrument for promoting literate communities in Nigeria. Our experience in using newspapers to enhance integrative writing and reading in language arts, social studies, science and mathematics in the formal set-ups in our communities will be shared in the paper.